The role of oxidative stress in Rett syndrome: an overview - De Felice, Claudio; Signorini, Cinzia; Leoncini, Silvia; Pecorelli, Alessandra; Durand, Thierry; Valacchi, Giuseppe; Ciccoli, Lucia; Hayek, Joussef (Annals of the New York Academy of Sciences, 2012)
The main cause of Rett syndrome (RTT), a pervasive development disorder almost exclusively affecting females, is a mutation in the methyl‐CpG binding protein 2 (MeCP2) gene. To date, no cure for RTT exists, although disease reversibility has been demonstrated in animal models. Emerging evidence from our and other laboratories indicates a potential role of oxidative stress (OS) in RTT. This review examines the current state of the knowledge on the role of OS in explaining the natural history, genotype–phenotype correlation, and clinical heterogeneity of the human disease. Biochemical evidence of OS appears to be related to neurological symptom severity, mutation type, and clinical presentation. These findings pave the way for potential new genetic downstream therapeutic strategies aimed at improving patient quality of life. Further efforts in the near future are needed for investigating the yet unexplored “black box” between the MeCP2 gene mutation and subsequent OS derangement.